2018
DOI: 10.1016/j.envint.2018.03.020
|View full text |Cite
|
Sign up to set email alerts
|

Pneumonia risk of people living close to goat and poultry farms – Taking GPS derived mobility patterns into account

Abstract: We previously observed an increased incidence of pneumonia in persons living near goat and poultry farms, using animal presence around the home to define exposure. However, it is unclear to what extent individual mobility and time spent outdoors close to home contributes to this increased risk. Therefore, the aim of the current study was to investigate the role of mobility patterns and time spent outdoors in the vicinity of goat or poultry farms in relation to pneumonia risk. In a rural Dutch cohort, 941 membe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 34 publications
(55 reference statements)
6
18
0
Order By: Relevance
“…The current results are also consistent with analyses using individual estimates of exposure to different livestock types in relation to primary care-registered data, showing an increased prevalence of pneumonia with higher livestock density [9,14,16]. This was also the case for studies including self-reported outcome assessments [29,30], despite that prevalence estimates based on self-reported questionnaires can deviate from those extracted from medical records [31,32]. Moreover, although less research has focused on respiratory patients, the higher rates of respiratory symptoms and infections we found in COPD patients in the exposed areas seem to be in agreement with findings of earlier studies in the Netherlands [17,18].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The current results are also consistent with analyses using individual estimates of exposure to different livestock types in relation to primary care-registered data, showing an increased prevalence of pneumonia with higher livestock density [9,14,16]. This was also the case for studies including self-reported outcome assessments [29,30], despite that prevalence estimates based on self-reported questionnaires can deviate from those extracted from medical records [31,32]. Moreover, although less research has focused on respiratory patients, the higher rates of respiratory symptoms and infections we found in COPD patients in the exposed areas seem to be in agreement with findings of earlier studies in the Netherlands [17,18].…”
Section: Discussionsupporting
confidence: 88%
“…Evidence suggests that prior infection with Coxiella burnetii, which is mostly found in goat farms and was the causative agent of the Q-fever epidemic in the Netherlands [13], could be a contributing factor to susceptibility to other infections [40][41][42]. However, the incidence of Q-fever in the last few years has dropped to pre-epidemic levels [21], and serological analyses in a subgroup of residents in the livestock dense areas showed no significant association between being seropositive for Coxiella burnetii and pneumonia history [29,30]. Although the Q-fever outbreak may have resulted in increased perceived risks of living close to goat farms, associations with pneumonia were not biased by residents who attributed their symptoms to farm proximity [43].…”
Section: Discussionmentioning
confidence: 99%
“…The evidence for this association resulted from several analyses on a large dataset of electronic medical records (2007–2013) of general practitioners’ (GP) patients living in the Dutch provinces Noord-Brabant and Limburg and on a subset of 2,500 of those patients that participated in a medical examination and completed a questionnaire [5, 913]. In this area, a major outbreak of Q fever, a zoonosis caused by Coxiella burnetii , occurred among goats in 2007–2010 [14] and had a significant public health impact on the nearby human population.…”
Section: Introductionmentioning
confidence: 99%
“…Residential proximity to goat farms was associated with an increased incidence of Q fever-related pneumonia [9]. In the years after the epidemic, the association between pneumonia and residence close to goat and other livestock farms was examined in several studies, which mostly indicated that the pneumonia incidence was still elevated among those living near goat farms [1113]. Potential causes of such elevation remain unclear and it has no clear trace to a single pathogen, as the evidence that microorganisms other than C .…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, one should keep in mind that infection of the resident may not necessarily take place at the residential location, i.e. movement by the resident around their residency and towards one of the infection sources may play a part [30], in particular for longer residential distances.…”
Section: Discussionmentioning
confidence: 99%